THE SOCIAL NATURE OF LANGUAGE IN SOCIOLINGUISTIC APPROACHES - N.T.Kuchimova (Journals Park Publishing, 2025)
This article analyzes the fact that sociolinguistics is a direction of linguistics that is inextricably linked with society, this area is not just the grammatical and phonetic structure of language, but how it is used in society, what social tasks it performs, and how it changes under the influence of social variables. It is also justified that sociolinguistics sees language as an active element of social life rather than as an abstract, ideal system.
Keywords: sociolinguistics, microsociolinguistics, macrosociolinguistics language, linguistics, society, thought, social factor.